Determination of Energy Dependence Level Density Parameter and its Application in Fission Products Calculation of Pu-238 - Abdul Waris; Rizal Kurniadi; Yuda S. Perkasa; Suwoto Suwoto (Institut Teknologi Bandung, 2008)
The energy dependence of level density parameter has been calculated using extended wood-saxon potential. The extended version of potential has deep well parameter that is independent to the nucleon density. The potential is pure central interaction. Although the potential is different from mean field theory, it gives the better result than that of the reference input parameter library-2 (RIPL-2). The application of the level density parameter results in small discrepancies from ENDF results. This method has been adopted in example for calculating fission products of Pu-238.